ANALISIS PENGARUH KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL, DAN KECERDASAN INTELEKTUAL TERHADAP KINERJA KARYAWAN - moniaga, pingkan (JURNAL RISET BISNIS DAN MANAJEMEN, 2013)
Bank Sulut Cabang Kantor Pusat is regional development bank number one who exists in north Sulawesi, PT. Bank Sulut sued for can also effectively employees. Bank employees north sulawesi headquarters having diversity in gender, old workings, and also education levels. These differences must be followed also by a difference level intelligence each employees. Differences on sex will be means comparison between intelligence intellectual on the majority man who dominant with logically, against emotional intelligence on the majority woman who dominant with his feelings. Engineering analysis of data using analysis chi-kuadrat discovered by helmet in 1900; and first reintroduced by karl pearson. The number of samples 208. The research of intellectual Quotient (IQ), emotional intelligence (EQ) and spiritual intelligence (SQ) owned by employees of the Head Office of PT. Bank Sulut partially or jointly affect significantly against its performance as an employee. Of the three types of human intelligence are examined, the intellectual intelligence that has the greatest impact and significantly to the performance of the employees of PT. Bank Sulut. Companies need to make the evaluation of employee performance and accompanied the EQ-IQ test at the beginning of the year. This evaluation is useful also for the employees, with the knowledge and ability of its performance, employees will be encouraged to work with a maximum of and compete to provide the best for his company. Key words: intelligence, emotional, spiritual, intellectual, performance